Accountability and Community Participation as Moderates on the Relationship between the Council's Knowledge of the Budget and Supervision of the Management of the Papua Special Autonomy Fund - Aprianto La’lang Kuddy (Syntax Corporation Indonesia, 2021)
The purpose of this study was to examine the effect of the knowledge of the members of the council about the budget on the supervision of the Papua special autonomy fund with accountability and community participation as moderating variables that will strengthen or weaken the relationship. The unit of analysis in this study is a member of the council at the office of the Papuan People's Representative Council (DPRP) and employees of the Regional Financial and Asset Management Agency of Papua Province. The number of respondents in this study were 111 respondents. Data was collected using direct surveys and the research hypotheses were tested using multiple regression analysis. The results of the study indicate that the board's knowledge of the budget variable has an effect on the supervision of Papua's special autonomy funds. In addition, it can also be proven that the interaction between public participation and knowledge of the budget affects the supervision of special autonomy funds. On the other hand, the interaction between accountability and the board's knowledge of the budget does not affect the supervision of special autonomy funds.